Agroforestry in Punjab - Current Status and Challenges - Sharm, Jitendra (Indian Forester, 1996)
This paper brings forth the natural resource setting and some of the socio-economic factors that influence the Agroforestry practices in the State of Punjab. It also explores the role of the Forest Department, Wood-based Industries and the Banks in promoting Agroforestry in the State; bringing out the lessons learnt in implementation of various Agroforestry schemes. It also traces the ups and downs in adoption of Agroforestry species - especially Eucalyptus and Poplar - by the farmers in Punjab. The paper pinpoints the issues and challenges before the Forest Department in sustaining the momentum of Agroforestry in the State.